A new allele of the kappa-casein gene in local zebu cattle breeds. Issue 1 (16th November 2017) - Ahmad, Tauseef; Atkulwar, Ashwin; Farah, Sameera; Singh, Vijendra; Baig, Mumtaz
Abstract : Local zebu cattle breeds in Indian villages are crossbred with exotic breeds at an unprecedented rate without utilising the full potential of genomic technologies. In addition to agriculture produce, livestock, particularly cattle, constitute a vital source of livelihood for farmers in India. Age-old agricultural practices, errant monsoon, and frequent crop failures have resulted in Maharashtra having the highest number of farmer suicides in the country. Local cattle breeds are considered low-yield breeds and thus are primarily used as beasts of burden. Information on functional gene variants in Indian cattle breeds is scant and limited to PCR-RFLP study in few breeds. In this study, 32 samples from 8 cattle breeds were obtained from remote villages of Maharashtra state. By using the re-sequencing technology, we sequenced 403 bp of the exon IV CSN3 allele and inferred its haplotypes. From 32 samples, 14 genotypes (G1–G14) defined by 7 single-nucleotide polymorphisms (SNP's) were identified. From these 14 genotypes, we reconstructed 3 haplotypes (H01, H02, and H03) and estimated their frequencies. Of the 3 haplotypes, two (H01 and H03) corresponded to CSN3*B4 and CSN3*B and CSN3*H and CSN3*G alleles, respectively. The third haplotype H02 was identified as a new allele and differed from CSN3*B4 and CSN3*B and CSN3*H and CSN3 *G alleles by one nonsynonymous mutation at the position C5306T-Ile100Thr. The neighbour-joining tree reconstruction revealed haplotype sharing or hybridisation between B. t. indicus and B. t. taurus because the 3 haplotypes originated in this study clustered with A1, B2, B4, B, G, and H alleles, which were reported previously in both the subspecies of B. taurus . The occurrence of one new allele in a small sample size highlights the urgency to screen local zebu cattle breeds by using genomic tools for circumventing genetic erosion that is widespread in Indian villages in India.